Basic learning of form - Magda Mària Serrano; Sílvia Musquera Felip; Luis Beriain Sanzol (OmniaScience, 2018)
"Form is' what', Design is 'how'" (Kahn, 1960). Learning about the formal universe and the wide range of possibilities it offers should be one of the purposes of the early subjects in architectural studies. This article aims to explain the contents of a first course of architectural design and demonstrate how, using a methodology based on precise theoretical-practical tools and an active pedagogical dynamic, results are obtained that, on average, are very satisfactory. It shows that in twelve weeks' time, students have acquired the tools they need to approach any design problem from its form.